2023
DOI: 10.1021/acs.jctc.3c00139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Receptor–Ligand Restraint Schemes for Alchemical Absolute Binding Free Energy Calculations

Abstract: Alchemical absolute binding free energy calculations are of increasing interest in drug discovery. These calculations require restraints between the receptor and ligand to restrict their relative positions and, optionally, orientations. Boresch restraints are commonly used, but they must be carefully selected in order to sufficiently restrain the ligand and to avoid inherent instabilities. Applying multiple distance restraints between anchor points in the receptor and ligand provides an alternative framework w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…56 While this restraint scheme gives an exact expression for the restraint free energy, we deemed it very difficult to choose the anchor points a priori, especially given the our imprecise knowledge of the binding pose (which is likely to be highly dynamic). For an excellent recent comparison of restraint schemes for absolute binding free energies, we refer the reader to Clark et al 57 In SAMPL6, which also featured highly carboxylated hostsocta-acid (OA) and tetramethyl octa-acid (TEMOA)-participants using GAFF/AM1-BCC with TIP3P consistently underestimated DG (i.e. predicted tighter binding), 4 similar to our results.…”
Section: Correcting For the Free Energy Bias Of Restrained Ligandssupporting
confidence: 86%
See 1 more Smart Citation
“…56 While this restraint scheme gives an exact expression for the restraint free energy, we deemed it very difficult to choose the anchor points a priori, especially given the our imprecise knowledge of the binding pose (which is likely to be highly dynamic). For an excellent recent comparison of restraint schemes for absolute binding free energies, we refer the reader to Clark et al 57 In SAMPL6, which also featured highly carboxylated hostsocta-acid (OA) and tetramethyl octa-acid (TEMOA)-participants using GAFF/AM1-BCC with TIP3P consistently underestimated DG (i.e. predicted tighter binding), 4 similar to our results.…”
Section: Correcting For the Free Energy Bias Of Restrained Ligandssupporting
confidence: 86%
“…56 While this restraint scheme gives an exact expression for the restraint free energy, we deemed it very difficult to choose the anchor points a priori , especially given the our imprecise knowledge of the binding pose (which is likely to be highly dynamic). For an excellent recent comparison of restraint schemes for absolute binding free energies, we refer the reader to Clark et al 57…”
Section: Resultsmentioning
confidence: 99%
“…The calculation of accurate absolute binding free energies of protein–ligand complexes is an essential and challenging task in computer-aided drug design (CADD). Many algorithms have been developed for this purpose, ranging from end-point alchemical methods to collective variable (CV)-based enhanced sampling algorithms. Ease of use, speed, automation, and reliability of the algorithm are particularly important aspects in the context of drug discovery pipelines. In this respect, nonequilibrium alchemical techniques have been shown to strike a good balance and be a valid alternative to traditional equilibrium alchemical techniques (FEP), , while they are generally easier to automate than CV-based enhanced sampling algorithms, such as Metadynamics. , …”
Section: Introductionmentioning
confidence: 99%
“…One way to overcome this issue is to perform very long simulations to fully sample the slow degrees of freedom associated with long-lived waters and the repositioning of lateral chains, but this approach is extremely computationally demanding. On the shorter time scales that are routinely employed, it has been recently shown that carefully selected restraints between the protein and the ligand greatly help the convergence. However, the resulting binding affinities depend critically on the initial choice of binding pose, which determines the accuracy of the predictions. …”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have mainly focused on the six-degree-of-freedom harmonic restraints, which are still widely used ,, and also face several problems. (1) The restraint addition is typically based on the researcher’s understandings about the interaction between the receptor and the ligand, which is inconvenient for inexperienced researchers and difficult to handle a large number of ligands.…”
Section: Introductionmentioning
confidence: 99%